Diseño de un manual de buenas prácticas, para el proceso de elaboración de yogurt en la pasteurizadora “San pablo”, Cantón Guano. - Escudero Saltos, Dennys Alexander (2026)
The objective of this research was to design a Good Manufacturing Practices (GMP) Manual for the yogurt production process at the “San Pablo” Pasteurizing Plant, located in Guano Canton, Chimborazo province. The study arose due to the frequent rejection of yogurt batches, mainly associated with food safety failures resulting from deficiencies in container sealing and improper handling. Analytical tools such as the Ishikawa diagram and the cause interrelation matrix were applied to identify the main factors responsible for the problem. The diagnosis was carried out using checklists based on the ARCSA-DE-2022-016-AKRG regulation, which allowed the determination of the plant’s initial level of GMP compliance. Statistical methods were also used to quantify rejection rates and test hypotheses related to product safety. The results showed that the main causes of rejection were the absence of a GMP manual, unsafe products, and improper container handling. Based on this, a technical manual tailored to the specific conditions of the plant was proposed, with standardized procedures, control formats, and corrective measures aimed at strengthening food safety. The implementation of the manual will help reduce the rejection rate of finished products, improve hygienic-sanitary conditions, and ensure compliance with current regulations, thereby contributing to the improvement of the company’s quality and competitiveness in the local market.